Attraction policies for digital nomads: some emerging issues - Serpa, Sandro; Sá, Maria José; Lalanda Gonçalves, Rolando (Frontiers in Human Dynamics, 2024)
The digital nomad phenomenon takes on a growing relevance in a digitalized society. This position paper aims to contribute to the analysis of the phenomenon of attraction policies for digital nomads, in its advantages, limitations and motivations, so as to justify a political and social intervention that is intended to be rigorously based.